Knockdown of the fat mass and obesity gene disrupts cellular energy balance in a cell-type specific manner. - Ryan T Pitman; Jason T Fong; Penny Billman; Neelu Puri (PLoS ONE, 2012)
Recent studies suggest that FTO variants strongly correlate with obesity and mainly influence energy intake with little effect on the basal metabolic rate. We suggest that FTO influences eating behavior by modulating intracellular energy levels and downstream signaling mechanisms which control energy intake and metabolism. Since FTO plays a particularly important role in adipocytes and in hypothalamic neurons, SH-SY5Y neuronal cells and 3T3-L1 adipocytes were used to understand how siRNA mediated knockdown of FTO expression alters cellular energy homeostasis. Cellular energy status was evaluated by measuring ATP levels using a luminescence assay and uptake of fluorescent glucose. FTO siRNA in SH-SY5Y cells mediated mRNA knockdown (-82%), increased ATP concentrations by up to 46% (P = 0.013) compared to controls, and decreased phosphorylation of AMPk and Akt in SH-SY5Y by -52% and -46% respectively as seen by immunoblotting. In contrast, FTO siRNA in 3T3-L1 cells decreased ATP concentration by -93% (p<0.0005), and increased AMPk and Akt phosphorylation by 204% and 70%, respectively suggesting that FTO mediates control of energy levels in a cell-type specific manner. Furthermore, glucose uptake was decreased in both SH-SY5Y (-51% p = 0.015) and 3T3-L1 cells (-30%, p = 0.0002). We also show that FTO knockdown decreases NPY mRNA expression in SH-SY5Y cells (-21%) through upregulation of pSTAT3 (118%). These results provide important evidence that FTO-variant linked obesity may be associated with altered metabolic functions through activation of downstream metabolic mediators including AMPk.